Identification of human interference and its impact on forest canopy density in the forested areas of Odisha, India - Basu Roy, Tanushree; Dutta, Dipanwita (Ecological Questions, 2025)
Forests are among the most vital and indispensable components of our ecosystems. However, increasing population pressure and associated infrastructural development have led to significant degradation of forest resources, particularly in developing regions. This study examines the temporal dynamics of forest canopy density over a 30-year period and identifies areas of disturbance within the forested landscapes of Keonjhar and Sundargarh districts, situated in northern and north-western Odisha, India. Forest canopy density changes were assessed using Landsat imagery from 1988 and 2021. Remote sensing-based biophysical indices such as AVI, BSI, and SSI were employed to develop a forest canopy density (FCD) model. Results indicate that approximately 17% of the forested area has been converted to bare land, and nearly 10% of the dense and moderately dense forested area has been converted to open forest in this period. Additionally, secondary datasets, including road networks, railway lines, mining areas, settlements, and industrial zones were integrated to analyze human-induced disturbances and delineate disturbance zones within the forests. A trend analysis of NDVI from 1988 to 2021 was conducted to validate these zones. Increasing mining activities, infrastructure development, settlement growth, and industrial waste dumping are identified as primary contributors to the increasing disturbance within the forest ecosystems of Keonjhar and Sundargarh districts. These findings highlight the urgent need for sustainable forest management and conservation strategies in this region.